Feasibility Analysis of Implementation 3G Macro Additional Sector JABO Area using Techno-Economic Approach - Iwan Krisnadi; Intan Kumalasari Tanjung (InComTech : Jurnal Telekomunikasi dan Komputer, 2016)
The increasing number of operators, making competition in the telecommunications industry are becoming increasingly stringent. These circumstances spurred operators to compete in achieving the best quality of services. Macro Additional 3G Sector (LTC) Project is one effort of the operator in maintaining the quality of data services. The general philosophy of the design of telecommunications networks are getting the best performance with minimal implementation costs. In this work will be analyzed with the techno-economic approach for the feasibility of the implementation of 3G Macro Additional Sector Project by operator telecommunication in Jakarta. Analysis model used is based on the principle of techno-economic by throughput and number of user approach with bottom-up models, to determine the design of 3G Macro Additional Sector Project, and then measure the feasibility of the costs incurred for the implementation of 3G Macro Additional the Sector Project.